2002
DOI: 10.1902/jop.2002.73.11.1260
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of Laser Irradiation on Cementum‐Bound Endotoxin Isolated From Periodontally Diseased Roots

Abstract: The Nd:YAG laser varying from 50 mJ, 10 pps to 150 mJ, 20 pps, for 2 minutes, did not seem to be effective in destroying diseased cementum endotoxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Liu et al. (110) explored the in vitro effectiveness of the Nd:YAG laser for the elimination of cementum‐bound endotoxin by measuring interleukin (IL)‐1β changes in stimulated monocytes. Nd:YAG laser varying between 50 mJ/pulse and 10 Hz and 150 mJ/pulse and 20 Hz for 2 min did not seem to be effective in destroying diseased cementum endotoxin.…”
Section: Basic Studiesmentioning
confidence: 99%
“…Liu et al. (110) explored the in vitro effectiveness of the Nd:YAG laser for the elimination of cementum‐bound endotoxin by measuring interleukin (IL)‐1β changes in stimulated monocytes. Nd:YAG laser varying between 50 mJ/pulse and 10 Hz and 150 mJ/pulse and 20 Hz for 2 min did not seem to be effective in destroying diseased cementum endotoxin.…”
Section: Basic Studiesmentioning
confidence: 99%
“…One hundred microliters of supernatant was added to an endotoxin-free tube and mixed with 100 µL of Limulus reagent. In the presence of endotoxins, the factors in LAL kits were activated in a proteolytic cascade that result in the cleavage of a colorless artificial peptide substrate [ 51 ]. Operated according to the operation manual and measured the absorbance at 545 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al (4) investigated the effect of Nd:YAG laser on the endotoxin in extracted teeth due to periodontal disease. They found that the laser itself could not produce temperature high enough to remove cement-bound endotoxin and at the same time be in safe clinical limits.…”
Section: Nd:yag Laser As An Adjunct To Nonsurgical Periodontal Therapymentioning
confidence: 99%